The philosophical basis and artistic characteristics of contemporary Western painting - Jiawei Wang (Trans/Form/Ação, 2024)
The guiding role of philosophical thinking, in artistic creation and development, is one of the important factors determining the direction of contemporary painting art. Different philosophical perspectives and trends have had a profound impact on the artists’ perspectives and creative methods. The characteristics of contemporary Western painting art demonstrate the subversion and alienation of tradition, and highlight individual and ethnic characteristics. The study explores the artistic characteristics and philosophical origins of contemporary Western painting as the main direction, and analyzes the impact of modern aesthetics, art markets and philosophical thinking on Western modern art. This diversity makes contemporary Western painting works more diverse and complex, blending with contemporary society and aesthetic tastes, constantly promoting the development and changes of art.